Uma história dos divertimentos do sul mineiro: Itajubá, Pouso Alegre e Campanha entre o final do século XIX e as primeiras décadas do século XX(1891-1930) - João Martins Nogueira Junior (2017)
This study focuses in a historical research on the main amusements that occurred in the southern region of Minas Gerais-Brazil between the last decade of the nineteenth century and the early decades of the twentieth century (1891-1930), analyzing their representations through the newspapers of the cities of Campanha, Pouso Alegre and Itajubá. At that time, the progress and modernity ideals were in vogue, which influenced the political, economic and cultural circumstances of the region. The methodology applied in this research was a documental analysis on press and a "Study of Amusement" was carried out, which consider temporal excerpt prior to modernity and within its scope, since the new forms of amusement that arose did not immediately replace the prior ones. The term "amusement" was recurrent on newspapers, and its reference was found along religious festivities, where sacred and profane characteristics influenced each other. In addition, population used to amuse by circuses that passed by attracting curious people to their shows and to the theatrical companies with their comedies and dramas presentations. The region was still the scene of festivities around the carnival days and the railway inauguration, providing moments of sociability, amusement and the sense of belongingness to each social segment. The Press focused these moments, inspired by the ideals of progress and civility, which also influenced the amusements accordingly with morality and good manners, such as licit and illicit games, vagrancy and prostitution, which were constitutive elements in that time peoples amusements. Data obtained from newspapers were impregnated with particular meanings from those who wrote in their pages, where the announcement of amusements were control strategies, but also permeated by contradictions where the old and the new were influenced by each other and were part of the outlook for the future, but with a focus on the traditions and values that persisted in continuing also in the recreational life of those who inhabited the region.